Early childhood nutrition, schooling, and sibling inequality in a dynamic context: evidence from South Africa - Yamauchi, Futoshi (International Food Policy Research Institute, 2006)
While nutritional intake in early childhood provides the basis for a child’s health capital, investments in schooling provide the basis for a child’s knowledge capital. That store of knowledge, in turn, will eventually be rewarded in the labor market. Does the good health built up by the child in his early years affect his educational achievement and his future success? This paper addresses that question based on panel data from South Africa.